(untitled) (GEOmedia, 2022)
For some years we have been hearing about “Smart Cities”, and this concept is rapidly evolving towards that of a digital twin that can support the modification, construction and evolution of the city. In order to develope this model we need a computer support suitable for simulation: the “mobile vehicle laserscanner” is today the technology that best suits this type of application, since it allows the survey through spherical photographic sensors and lidar of millions of points per second, resulting among the most suitable means for the massive mapping of the city. With this technology it is possible to acquire geospatial information from the ground at a scale suitable for most of the needs of urban applications at speeds typical of urban traffic, as has been highlighted by the survey carried out by GRS for the Municipality of Rome. GRS is an engineering, geodesy and nondestructive investigation technology company based in Rome, which has been employing laserscanner technology since the dawn of this technology. In the case study examined, the survey was carried out by means of the high-performance and latest-generation Riegl VMQ-1HA mobile laserscanner system, equipped with a Ladybug 5+ camera for the generation of panoramic photos and the coloring of the point cloud. The survey was carried out in 3 characteristic districts of the city of Rome, namely some main streets of Testaccio, Trastevere and EUR and generated a cloud of points with an extension of about 30,000 square meters with a road development of about 1.4 km, for a significant time of about three hours. Once the acquisition is completed, carried out at a speed similar to that of vehicular traffic, the individual clouds acquired by the instrument are processed on a PC, using the instrument’s return software, such as Riegl RiPROCESS. In the following we experimented with different ways of returning the cloud, for example through the Orbit 3DM Feature Extraction software, which thanks to its ability to automatically and semi-automatically classification, it recognize the objects of which the point cloud is composed. For this reason it was possible to create a specific database for each category of two- or three-dimensional object. The laser survey and the subsequent stacking of what is physically present is the founding pillar for any development of digital-twin and ultimately of smart city. The integration of the different new generation technologies will help the offices in charge in carrying out the best choices both in terms of safety for the city, and in terms of traffic management and any type of emergency.